Small Signal Stability Analysis of Kalimantan 500 KV Electricity System - Agus Sadid, Akbar Syahbani; Mutiarso, Ismayahya Ridhan; Arif, Fauzany; Muda, Kemal Iskandar; Prawira, Fadhil Bintang (Faculty of Advanced Technology and Multidiscipline Universitas Airlangga, 2023)
Small signal stability refers to the ability of a system to return to equilibrium after experiencing a small disturbance. In this research, the Kalimantan electricity system will be analyzed for the stability of its small signal. Analysis of the stability of small signals in electrical systems including local disturbances and inter-area disturbances. The Kalimantan system will be analyzed using Power Factory software. System analysis was carried out by evaluating the eigenvalues